2010
DOI: 10.3109/03014460.2010.513774
|View full text |Cite
|
Sign up to set email alerts
|

The search of a genetic basis for noise-induced hearing loss (NIHL)

Abstract: The findings suggest effects of familial history of hearing loss, of GSTT1 and GSTM1 enzymes and of mitochondrial haplogroup L1 on the risk of NIHL. This study also described novel sequence variants of MTRNR1 and MTTS1 genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 52 publications
1
17
0
7
Order By: Relevance
“…It consisted of 306 Brazilian unaffected individuals of various ethnic backgrounds: 133 subjects were predominantly of European ancestry, 165 were of predominantly African ancestry, and 8 were of Asian ancestry. Part of the control sample is described in Abreu-Silva et al (2010). The Brazilian population is highly admixed and subjects, with either European or African ancestry, may present high frequencies of Native American lineages of mitochondrial DNA (Bortolini et al, 1997;Alves-Silva et al, 2000;Marrero et al, 2005).…”
Section: Subjectsmentioning
confidence: 97%
“…It consisted of 306 Brazilian unaffected individuals of various ethnic backgrounds: 133 subjects were predominantly of European ancestry, 165 were of predominantly African ancestry, and 8 were of Asian ancestry. Part of the control sample is described in Abreu-Silva et al (2010). The Brazilian population is highly admixed and subjects, with either European or African ancestry, may present high frequencies of Native American lineages of mitochondrial DNA (Bortolini et al, 1997;Alves-Silva et al, 2000;Marrero et al, 2005).…”
Section: Subjectsmentioning
confidence: 97%
“…These include a variety of metabolic enzymes and heat shock proteins tied to redox regulation (Yang, et al, 2006; Konings, et al 2007; Lin, et al, 2010; Liu, et al, 2010a, b; Abreu-Silva, et al, 2011), ion channels and ion transport proteins, and structural and gap junction proteins (Van Laer, et al, 2006; Konings, et al, 2007; Slwinska-Kowalska, et al, 2008; Pawelczyk, et al, 2009). , These findings have been replicated for catalase (CAT) the heat shock protein HSP70, potassium ion channels (KCNQ4, KCNE1), myosin 14 (MYO14) and protocadherin 15 (PCDH15).…”
Section: Introductionmentioning
confidence: 99%
“…When participants were categorized as those with audiograms suggestive of NIHL (loss at 4000,6000, and/or 8000 Hz), those with other forms of hearing loss, and those with no loss, associations of the NIHL group with glutathione S-transferase mu 1(GSTM1), glutathione S-transferase theta 1(GSTT1) and mitochondrial haplotype 1 were observed (Abreu-Silva, et al, 2011). Examination of industrial workers, sorted by the amount of temporary threshold shift they exhibited after a day of work, revealed associations with GSTM1, GSTT1 and glutathione S-transferase pi (GSTP; Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ere are greater than 10 million workers employed in high-noise environments in China, of which at least 10% have different levels of hearing loss. Although environmental factors play a vital part in the development of NIHL, population epidemiologic studies have shown that, with the exception of the influence of other confounding factors, hereditary factors account for up to 50% of the variability in hearing loss after noise exposure [2,3].…”
Section: Introductionmentioning
confidence: 99%